Ebû Yûsuf'un fıkıh anlayışı - Ersoy, Hatice Engin (My University, 2019)
Hanefî mezhebinin kurucu imamlarından olan Ebû Yûsuf, mezheplerin oluşmaya başladığı, hadis tedvin ve tasnif çalışmalarının devam ettiği bir dönemde yaşamıştır. Ebû Hanîfe’nin ders halkasında yetişen Ebû Yûsuf, hocasının görüşlerini kaleme almak, bu görüşleri öğrencilerine aktarmak ve bu doğrultuda yeni meselelere hüküm vermek suretiyle Hanefi mezhebinde önemli bir rol oynamıştır. Yeni rivayetlere ulaşması, üstlendiği kadılık vazifesinin etkisi ve hocasıyla gözettikleri ilkelerin farklılığı sonucunda bazı meselelerde Ebû Hanîfe’den ayrı görüşlere sahip olmuş, bu durum mezhebin güncellik ve zenginlik kazanmasına katkıda bulunmuştur. Bu çalışmada Ebû Yûsuf’un fıkıh anlayışının arka planını oluşturan unsurlar incelenmiş, daha çok kendisinin elimize ulaşan eserleri bağlamında usul görüşleri ve onun fıkıh anlayışını özgün kılan hususlar tespit edilmeye çalışılmıştır.

Abû Yûsuf, one of the founding imams of the Hanafî school of law, lived in a period when the schools of law began to form, and the written record and classification of hadith studies continued. Abû Yûsuf, who was educated in the student circle of Abû Hanifa, played an important role in the Hanafî school of law by writing the views of his teacher, conveying these views to his students and ruling on new issues in this direction. As a result of his access to narratives, his role as a judge and the different principles he upheld from his teacher, he had different legal opinions from Abû Hanifa on some issues contributed to the legal school acquiring greater currency and diversity. As such, this study examines the elements that constitute the background of Abu Yûsuf’s understanding of fiqh in the context of his extant works and attempts to determine the qualities that make his understanding of fiqh distinctively unique.
Keywords: Abu Hanifa; Ebu Hanife; Ebu Yusuf; Fıkıh; Fiqh; Hanafi Sect; Hanefi Mezhebi; Islam; Islamic law; İslam; İslam hukuku; Kadı Abu Yusuf; Qadi